Evaluation the Quality and Safety of Raw Table Eggs in North Palestinian Markets - Mohammed Sabbah; Asmaa Al-Asmar (مجلة جامعة النجاح للأبحاث العلوم الطبيعية)
This study aimed to evaluate the quality and safety of retail raw table eggs in north Palestinian markets. In this study, 480 eggs were collected in two different periods from various retail markets, both Palestinian governorates Tulkarm and Jenin. All collected eggs were evaluated for their safety and external and internal quality. The results showed that about 40.0% of the collected samples had eggshell abnormalities. A high variation in the egg's weight was detected in the eggs collected from Tulkarm. According to the Haugh unit, the results indicated that the most collected eggs were in class B. The average yolk color score of all periods in both governorates is around 8. Some eggs had yolk pH values of more than 6.6 in both governorates. Most collected eggs in both periods and governorates were fresh according to the yolk index. Escherichia coli was present in the eggshell collected from Jenin governorate. Meanwhile, Salmonella enteritidis was present in Tulkarm governorate. In conclusion, this study confirms that grading, cleaning, and cooling is not practiced before the sale, which may lead to microbiological health hazard to the general public. Thus, this study recommends avoiding eating raw or undercooked egg yolks and whites or their products.